TOWARDS A CULTURE OF BIODIVERSITY CONSERVATION - Halffter, Gonzalo (Instituto de Ecología, A.C., 2005)
This article is intended as a synthesis of the ideas, previously presented by the author, on the conservation of biodiversity as well as new proposals, heretofore unpublished. The author focusses on the central theme that in each society the ideas held about the use and the conservation of biodiversity and, in more general terms, about nature are an integral part of the culture of that society, and as such cannot be separated from its ethical and aesthetic values, or from its socio-economic reality. Three broad approaches to the protection and use of species richness are considered: rustic use, the establishment of protected areas and land use policy. Three types of protected areas are examined: hunting or game reserves, national parks and biosphere reserves. These conservation strategies appeared at different points in history in response to different needs and are therefore not mutually exclusive. They share the goal of protecting the exceptional richness of animals and plants within a delimited area. The problems facing these approaches, given the increasing evidence of spatial exchange of species, i.e. beta diversity, are examined. A single area is not enough to protect beta diversity, even when it is a big one. In response to this dilemma a completely new alternative is proposed, one that is complementary to the three currently in use – that of archipelago reserves.